2005
DOI: 10.2105/ajph.2004.042879
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomonitoring to Optimize Fish Consumption Advice: Reducing Uncertainty When Evaluating Benefits and Risks

Abstract: National fish consumption advisories that are based solely on assessment of risk of exposure to contaminants without consideration of consumption benefits result in overly restrictive advice that discourages eating fish even in areas where such advice is unwarranted. In fact, generic fish advisories may have adverse public health consequences because of decreased fish consumption and substitution of foods that are less healthy. Public health is on the threshold of a new era for determining actual exposures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In a study of Swedish women of child-bearing age, 127 women reported consuming, on average, four fish meals/week and had a median hair mercury level of 0.70 mg/kg (Bjornberg et al 2005). A study of 150 pregnant women from varied locations in Alaska found somewhat lower levels: The median hair mercury was 0.47 mg/kg and the mean was 0.72 mg/kg (Arnold et al 2005). Two studies—one from Massachusetts, the other from southwest Québec—reported mercury levels more similar to those in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Swedish women of child-bearing age, 127 women reported consuming, on average, four fish meals/week and had a median hair mercury level of 0.70 mg/kg (Bjornberg et al 2005). A study of 150 pregnant women from varied locations in Alaska found somewhat lower levels: The median hair mercury was 0.47 mg/kg and the mean was 0.72 mg/kg (Arnold et al 2005). Two studies—one from Massachusetts, the other from southwest Québec—reported mercury levels more similar to those in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that there exists a strong relationship between eating and mood, and that diet and particular dietary constituents can have important influences on behaviour, including alertness and mental performance [1][2][3]. Wurtman RJ and Wurtman JJ [1] developed the hypothesis that carbohydrates can relieve depression because that carbohydrate intake enhanced serotonin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Peter J. Rogers' [5] studies that have shown substantially increasing EPA and DHA intake for 3 months was found not to have beneficial or harmful effects on mood in mild to moderate depression. With respect to energy expenditure, it is known that protein has the highest and most prolonged thermic effect of the separate macronutrients (20 -30%), followed by carbohydrate (5 -15%) and fat (0 -3%) [3]. Protein has been observed to increase satiety to a greater extent than carbohydrate and fat and therefore can reduce energy intake [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This panel called by the Harvard Center for Risk Analysis suggested that substituting low MeHg concentration fish with high level concentration fish yielded substantial prenatal cognitive developmental benefits and few negative impacts for women of childbearing age. Arnold et al (2005) pointed out the risk of overly restrictive fish consumption advice. What one does not see from the aforementioned studies is the actual fish consumption trend in the recent decade for the general public as a whole and pattern of fish consumption by high-risk population cohorts.…”
Section: Literature Reviewmentioning
confidence: 99%